2019
DOI: 10.1021/acs.cgd.8b01489
|View full text |Cite
|
Sign up to set email alerts
|

Wheel and Axle Topology Driven Halogen Bonds for the Construction of Molecular Arrays in Hexacoordinated Sn(IV)Porphyrins: A Structural and Theoretical Investigation

Abstract: The present study illustrates how halogen bonds (XB) in conjunction with judiciously selected molecular scaffolds can be used for the construction of molecular arrays (ladder, one-dimensional (1D), and two-dimensional (2D) frameworks) in a series of Sn­(IV)-porphyrin derivatives, which topologically resemble a “wheel–axle” duo. In all the complexes investigated here, the wheel is constructed with Sn­(IV)-5,10,15,20-meso-tetrakis­(4-bromophenyl)­porphyrin [Sn­(L)2-TBrPP], which is relatively rigid, and the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…The calculate σ‐hole potential shows V S,max values close to +12.5 kcal mol −1 [58] . The presence of the σ‐hole is in full agreement with earlier theoretical studies reported by us and others in the literature [58—62,17–20] …”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The calculate σ‐hole potential shows V S,max values close to +12.5 kcal mol −1 [58] . The presence of the σ‐hole is in full agreement with earlier theoretical studies reported by us and others in the literature [58—62,17–20] …”
Section: Introductionsupporting
confidence: 89%
“…[58] The presence of the σ-hole is in full agreement with earlier theoretical studies reported by us and others in the literature. [58][59][60][61][62][17][18][19][20]…”
Section: Theoretical Analysismentioning
confidence: 99%
“…In the structure of 1 , the axial chloro ligand interacts with the pyrrole ring of adjacent porphyrin unit, with distances of 3.507 Å (Cl⋯centroid) and 3.419 Å (Cl⋯C β ) (Figure 3). 42 Weak Cl–Cl interactions were also found between the axial chloro ligands with a distance of 4.568 Å. Consequently, the square structural motifs of the stacked 2D layers were well aligned, forming porous channels in 1 .…”
Section: Resultsmentioning
confidence: 96%
“…In our previous work on six coordinated tin-porphyrin complexes, [29][30][31] we observed an interesting phenomenon in the solid phase. The location of the halogen bond donor or acceptor on the porphyrin plays a critical role in the self-assembly process.…”
mentioning
confidence: 87%